Subjective Rights in the Modern Legal Paradigm (According to the Results of the Inter-University Scientific-Practical Conference “Baskin’s readings”) - I K. Shmarko (Теоретическая и прикладная юриспруденция)
Currently, public relations, government and legal regulation are undergoing transformation. Used legal institutions and instruments require rethinking and filling with new meanings. One of the legal categories that require in-depth theoretical analysis in order to adequately modern law enforcement conditions is the institution of subjective rights. The first Interuniversity scientific-practical conference “Basking readings” was devoted to the analysis of this problem, according to the impressions of which this essay was written.